A study to assess the impact of left atrial size reduction in outcome of the patients undergoing mitral valve surgery for mitral valve disease with left atrial enlargement in a tertiary care hospital - K. H., Raghavendra; A., Chandra (International Surgery Journal, 2021)
Background: Rheumatic mitral valve disease (mitral stenosis or regurgitation) remains the common heart disease in developing countries. Mitral valve is involved in 99% of cases. The prognostic implication of LA (left atrium) size has also been shown in high-risk subgroups, such as patients with acute myocardial infarction, atrial arrhythmia, LV dysfunction, or dilated cardiomyopathy, and patients undergoing valve replacement for aortic stenosis and mitral regurgitations. Objective of the study was to study the impact of left atrial size reduction in patients undergoing mitral valve surgery for mitral valve disease with left atrial enlargement on clinical outcome and echocardiographic parameters. Methods: A prospective study was done at department of cardiovascular and thoracic surgery, Sri Venkateshwara institute of medical sciences, Tirupati from June 2012 and June 2013.The study population consisted of patients with rheumatic mitral valve disease with or without tricuspid valve disease with left atrial size enlargement who underwent mitral valve surgery alone and mitral valve surgery with left atrial reduction. Twenty consecutive subjects were taken in each group during the study period. Results: The age range is 21 to 61 years. There means age is 39.7±10.3 years. in the study group. Following MVR significant improvement in the NYHA (New York Heart Association) functional class was noted in all the patients. The decrease in RVSP, LA size, and TR was noted in all the patients. Conclusions: It seems reasonable to suggest that patients who undergo LA reduction along with MVR have significant improvement in clinical outcome and NYHA functional class with less thromboembolic complications during long term follow up.